PROGRAM PENGABDIAN MASYARAKAT PRO LINGKUNGAN: PEMANFAATAN MINYAK GORENG BEKAS DAN PLASTIK DI TANJUNG PINGGIR - Lubis, Abdullah Mubarak; Lubis, Ekki Wahyuni; Reyvani, Divya; Syahputra, Inal; Nasution, Mulkan Iskandar (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The issue of waste is a major problem faced by the community in Tanjung Pinggir Village, Siantar Martoba District. The existence of a waste bank in the village has not been able to fully address environmental problems caused by the accumulation of plastic waste and household waste in the form of used cooking oil. This Community Service Program (KKN) was carried out with the aim of raising public awareness of the importance of protecting the environment through an ecotheology approach. The implementation methods included processing used cooking oil into aromatherapy candles for teenage girls and mothers, and processing plastic waste into paving blocks for teenage boys and fathers. The results of the activities showed that the community was receptive and actively involved in processing waste into useful products. Aromatherapy candles and paving blocks are not only a solution for waste reduction, but also have the potential to be developed into micro, small, and medium enterprises (MSMEs) for the local community. The ecotheology approach, through the understanding that humans are caliphs on earth who are obliged to preserve it, is able to provide a religious dimension to pro-environmental activities. Thus, this activity contributes to community empowerment while supporting sustainable development.